2018
DOI: 10.1371/journal.pone.0194657
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial evaluation of red, phytoalexin-rich sorghum food biocolorant

Abstract: Sorghum (Sorghum bicolor) extract is traditionally used as red biocolorant in West Africa to colour foods, among which wagashi, a soft cheese. This biocolorant is a source of the phytoalexin apigeninidin and phenolic acids, and users claim that it has preservative effects next to its colouring properties. If such a claim can be scientifically substantiated, it adds a valuable functional property to this natural red colorant, thereby increasing its potential applications in the food industry. Hence, the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…Questions of which specific compound(s) in sorghums has efficacy, and the representation of those compound(s) in the diversity of sorghum was not in the scope of this project. Furthermore, a second limitation was that only two species of Gram-positive bacteria were tested, but the findings are similar to other researchers [ 32 , 44 ]. Akogou et al [ 44 ] demonstrated no antimicrobial activity of red, phytoalexin-rich sorghum extract against E. coli O157.…”
Section: Discussionsupporting
confidence: 80%
“…Questions of which specific compound(s) in sorghums has efficacy, and the representation of those compound(s) in the diversity of sorghum was not in the scope of this project. Furthermore, a second limitation was that only two species of Gram-positive bacteria were tested, but the findings are similar to other researchers [ 32 , 44 ]. Akogou et al [ 44 ] demonstrated no antimicrobial activity of red, phytoalexin-rich sorghum extract against E. coli O157.…”
Section: Discussionsupporting
confidence: 80%
“…3-Deoxyanthocyanidins are also plant phytoalexins with antimicrobial activity. Studies have demonstrated that 3deoxyanthocyanidins are effective against a range of fungi and bacteria in vitro (Aida, Tamogami, Kodama, & Tsukiboshi, 1996;Stonecipher, Hurley, & Netzly, 1993), although a recent study showed no significant antimicrobial effect on an African food Wagashi (Akogou, Besten, Kayode, Fogliano, & Linnemann, 2018). Nevertheless, 3-deoxyanthocyanidins could play a role in food preservation, reducing and possibly replacing the synthetic antimicrobial additives in foods.…”
Section: The Potential Application Of Sorghum Phenolic Compoundsmentioning
confidence: 99%
“…In contrast, sorghum crude stem extract showed high inhibition against P. aeruginosa (gram-negative) compared to B. subtilis (gram-positive) [3]. On the other hand, extracts of dye sorghum leaf sheaths found have no anti-bacterial properties on E. coli tested in a nutrient-rich traditional West African cheese [5]. However, similar trends of exerting higher activity against gram-positive bacteria compared to gram-negative strains have been also reported on seed extracts of sorghum.…”
Section: Antimicrobial Activity Of Sorghum Leavesmentioning
confidence: 95%
“…Other important uses, especially from leaves, sheath, stalks, glumes, and root were also available including food additives and folk pharmaceuticals. Red or purple pigments are largely extracted from the sheath and used as food colourants such as cheese and porridges, and dyes for leather, textile, and wood in numerous countries of Africa and Asia [3][4][5]. Sorghum extracts is reported to have antiabortion, cyanogenic, demulcent, diuretic, emollient, intoxicant, and toxic properties [6].…”
Section: Introductionmentioning
confidence: 99%